New Perspectives on Nitrogen Fixation Measurements Using 15N2 Gas - Wannicke, Nicola; Benavides, Mar; Dalsgaard, Tage; Dippner, Joachim W.; Montoya, Joseph P.; Voss, Maren (Frontiers in Marine Science, 2018)
Recently, the method widely used to determine 15N2 fixation rates in marine and freshwater environments was found to underestimate rates because the dissolution of the added 15N2 gas bubble in seawater takes longer than theoretically calculated. As a solution to the potential underestimate of rate measurements, the usage of the enriched water method was proposed to provide constant 15N2 enrichment. Still, the superiority of enriched water method over the previously used bubble injection remains inconclusive. To clarify this issue, we performed laboratory based experiments and implemented the results into an error analysis of 15N2 fixation rates. Moreover, we conducted a literature search on the comparison of the two methods to calculate a mean effect size using a meta-analysis approach. Our results indicate that the error potentially introduced by an equilibrium phase of the 15N2 gas is -72% at maximum for experiments with very short incubation times of 1 hour. In contrast, the underestimation was negligible for incubations lasting 12 to 24 hours (error is -0.2%). Our meta-analysis indicates that 84 % of the measurements in the two groups will overlap and there is a 61% chance that a sample picked at random from the enriched water group will have a higher value than one picked at random from the bubble group. Overall, the underestimation of N2 fixation rates when using the bubble method relative to the enriched water method is highly dependent on incubation time and other experimental conditions and cannot be generalized.